Pendidikan Kesehatan Gaya Hidup Sehat dan Gizi Seimbang Dalam Mengoptimalkan Kesehatan Remaja : Studi Kasus - Wicaksono, Erdi Ramdhan Tri; Mulya, Adelse Prima; Purnama, Dadang (Universitas Malahayati, 2023)
ABSTRACT Adolescence is a period of transition from the childhood phase to the adult phase with an age range of 10 - 19 years. Adolescents are an age group that is vulnerable to malnutrition or overnutrition. Indonesia is currently faced with a triple burden of nutrition problems, namely nutritional deficiencies (stunting and wasting), excess nutrients (obesity) and micronutrient deficiencies such as anemia. Food and nutrition knowledge is also one of the factors that affect nutritional status so that health education is needed related to nutrition formally and non-formally which aims to improve nutrition and health knowledge of adolescents. The purpose of this study was to determine the increase in adolescents' knowledge about healthy lifestyles and balanced nutrition with health education interventions in optimizing adolescent health. This research uses a case study design. The population in this study were adolescents in the environment of SMP Vijaya Kusuma Bandung as many as 411 adolescents. The sampling technique in this study was carried out by non-probability sampling, namely total sampling, this technique was used to make all populations as samples. The assessment was carried out for four days, on April 03 to 06, 2023, health education intervention was carried out for one day, on April 13, 2023 by proposing the theme of Healthy Lifestyle and Balanced Nutrition in Adolescents. Data analysis using Stastical Program for Social Science (SPSS) The results were presented with frequency and percentage distribution tables. The results of health education have increased pre-test and post-test scores by 33% with a comparison in the pre-test the average student managed to get a score of 5.9 points while in the post-test the average student managed to get a score of 7.88 points out of a total of 10 points. Based on the evaluation results, there was an increase in post-test scores in Vijaya Kusuma Junior High School students. This shows the impact of health education on student knowledge. Keywords: Adolescents, Healthy Lifestyle, and Balanced Nutrition ABSTRAK Masa remaja merupakan periode transisi dari fase kanak-kanak ke fase dewasa dengan rentang usia 10 – 19 tahun. Remaja merupakan kelompok usia yang rentan mengalami masalah gizi kurang ataupun lebih. Saat ini Indonesia dihadapkan pada tiga beban masalah gizi (triple burden) yaitu kekurangan nutrisi (stunting dan wasting), kelebihan nutrisi (obesitas) dan kekurangan zat gizi mikro seperti anemia. Pengetahuan pangan dan gizi juga merupakan salah satu faktor yang mempengaruhi status gizi sehingga diperlukan edukasi kesehatan terkait gizi secara formal maupun non formal yang bertujuan untuk meningkatkan pengetahuan gizi dan kesehatan remaja. Tujuan dalam penelitian ini adalah untuk mengetahui peningkatan pengetahuan remaja mengenai gaya hidup sehat dan gizi seimbang dengan intervensi pendidikan kesehatan dalam mengoptimalkan kesehatan remaja. Penelitian ini menggunakan desain studi kasus. Populasi pada penelitian ini adalah remaja di lingkungan SMP Vijaya Kusuma Bandung sebanyak 411 remaja. Teknik penarikan sampel dalam penelitian ini dilakukan dengan cara non probability sampling yaitu total sampling, teknik ini digunakan untuk menjadikan semua populasi sebagai sampel. Pengkajian dilaksanakan selama empat hari, pada tanggal 03 hingga 06 April 2023, intervensi pendidikan kesehatan dilaksanakan selama satu hari, pada tanggal 13 April 2023 dengan mengusul tema Gaya Hidup Sehat dan Gizi Seimbang pada Remaja. Analisa data menggunakan Stastical Program for Social Science (SPSS) disajikan dengan tabel distribusi frekuensi dan persentase. Hasil pendidikan kesehatan terdapat peningkatan nilai pre-test dan post-test sebesar 33% dengan perbandingan pada pre-test rata-rata siswa berhasil mendapatkan nilai 5.9 poin sedangkan pada post-test rata-rata siswa berhasil mendapatkan nilai 7.88 poin dari total 10 poin. Berdasarkan hasil evaluasi terdapat peningkatan nilai post-test pada mahasiswa SMP Vijaya Kusuma. Hal tersebut menunjukan adanya dampak dari pendidikan kesehatan terhadap pengetahuan siswa. Kata Kunci: Remaja, Gaya Hidup Sehat, dan Gizi Seimbang